Attention deficit hyperactivity disorder improved with Methylphenidate: a case report - Hamid, Farzana; Roy, Prakash Chandra (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: Attention deficit hyperactivity disorder (ADHD) is a neurobehavioral disorder characterized by either significant difficulties of inattention or hyperactivity and impulsiveness or a combination of the two. Objective: The case was discussed because its symptoms can be difficult to differentiate from other disorders, increasing the likelihood that the diagnosis of ADHD will be missed and with proper treatment, kids with ADHD can learn to successfully live with and manage their symptoms. Result: After 6 months of treatment with methylphenidate, the patient started to improve and at the end of 2 years he became a communicative boy, making good school progress with occasional setbacks. Conclusion: ADHD is often under diagnosed in children. So, early diagnosis and treatment is very important for prevention of long-term effects. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.41 Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 52-55